271 Trillion Makes Stocks Volatile - Farih Ayu Mukhoirotin Sirojul Umma Rosyihin; Sari, Herlinda Maya Kumala; Supardi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
It is essential for investors to assess the value of a company before deciding to buy or sell it. This study aims to provide an understanding, knowledge, and examination of the impact of corruption on stock prices. It tests the effect of ROE, DER and PBV on stock prices of companies in the mining sector listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period with a sample of 10 companies was selected using purposive sampling from the investment gallery located at Universitas Muhammadiyah Sidoarjo. Using E-Views 12 software and the analysis method is panel data regression. This study employs the Random Effect Model (REM). Based on the results of this study, that the DER and PBV don’t have a significant effect on stock prices. Meanwhile, ROE has a significant effect on stock prices. The conclusion is that the influence by DER and PBV are merely predictions.